Synthesis of A Novel Carrier Compound Thiazoethyl Methyl Eugenoxyacetate from Eugenol and Its Use in the Bulk Liquid Membrane Technique - Muhammad Cholid Djunaidi; Pratama Jujur Wibawa; Ratna Hari Murti (Universitas Gadjah Mada, 2018)
Research into the synthesis and use of a novel carrier compound, thiazoethyl methyl eugenoxyacetic acid (TMEAA) for selective transport of Cu(II), Cd(II) and Cr(III) metal ions in the bulk liquid membrane (BLM) technique was conducted. TMEAA was synthesized from eugenol. Eugenol was acidified into eugenoxyacetic acid and subsequently esterified using 4-methyl-5-thiazoethanol. Analysis of the result was performed using GC-MS and FTIR. The TMEAA obtained was liquid, viscous, blackish-brown and fragrant, with a yield of 88%. This compound was soluble in benzene and chloroform but insoluble in methanol. The GC-MS analysis result showed the presence of a single peak, with a retention time of 26.5 min and an area of 100%, while the disappearance of vibration mode at 1727 cm-1 was attributed to acid absorption and the FTIR spectrum indicated that formation of an ester group had occurred. TMEAA was used as a carrier compound in the BLM technique to transport Cu(II), Cd(II) and Cr(III), using chloroform as a solvent. The results showed that TMEAA was more selective for Cu(II) and Cd(II) than Cr(III). Moreover, the research proved that N and S groups of TMEAA were selective for Cu (II) and Cd (II).